J.Barnes, J.Fowles, and B.S. Johnson: case studies in the postmodern, the author, & text-editing - Emily, Heathcote (2020)
This thesis explores how practices of text-editing can shed new light on the utility of the terms ‘modernism’ and ‘postmodernism’ as ways of categorising mid- to late-twentieth-century fiction. The research does not aim to interrogate editorial theory or critical theory per se; but to bring these areas of the discipline into productive dialogue to further our understanding of what is meant by ‘radical’ or ‘subversive’ fiction, and the extent to which it resists interpretation. The thesis focuses on three works by three different authors: The Unfortunates by B.S. Johnson, The Magus by John Fowles, and Flaubert’s Parrot by Julian Barnes. These three novels have complex relationships with postmodernism, a label which, this thesis argues, is losing precision through overuse. I contest the categorisation of these three works as postmodern, arguing that there is value to be found in recognising their differences as well as their similarities. I call for the reinscription of the figure of the author into the text as a way of opening up new avenues of interpretation for the reader. I explore how an understanding of authorial persona, authorial intention, and the author’s creative processes can be a source of elucidation, particularly when a work has become historically distanced from a modern-day readership. The practices of text-editing are employed to demonstrate how a work like The Magus is not as radical as the postmodern label suggests it to be; how The Unfortunates is more subversive than indicated by the accusations of gimmickry and pejorative connotations of experimentalism that have hovered around the work since its publication; and how Flaubert’s Parrot, although decisively postmodernist, has subtle nuances of meaning that may be overlooked if the concept of the author is disregarded. As part of this discussion, I explore the ethics and implications of each author’s use of source material via appropriation, translation, and revision; and I show how an awareness of such processes gives us new insight into an author’s intentions. The argument is supported by archival research undertaken at the Harry Ransom Center and the British Library into authorial manuscripts and autograph notes. The thesis concludes by making a case for critical editions of these novels, along with other late twentieth-century novels that are becoming increasingly historical, with the view to reinvigorating interest in them.